O Desenho Técnico aplicado ao conteúdo da disciplina de Design de Joias e Bijuterias Liliane (ModaPalavra e-periódico, 2013)
The aim of this paper is to present how the Technical Standards ABNT are applied to design of products in the discipline of Jewelry Design in Fashion Design Course at Feevale, and highlight how the graphical representation and technical specification for a jewelry design and others products are extremely important for proper communication of a creative idea. Throughout the text is made to reflect on the record of the initial ideas, trials of composition, shapes, colors and materials, wich follows the volumetric study and orthogonal projections. The various pieces of adornment for the body should be unterstood in all its particularities, whether formal character, technical and usability. To this end, the theoretical framework and the literature used in this article are specific to this study. The methodology follows a practical applied in the classroom. The final considerations reinforce the importance of design process all day for a creative activity directed to industrial manufacturing.
Keywords: design; products; jewelry